THE ABILITY TO CORRECTLY DISTRIBUTE ATTENTION IN THE ACTIVITIES OF THE TEACHER (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
The distribution of attention is a key skill that significantly impacts the effectiveness of a teacher’s instructional delivery and classroom management. This article explores how attention distribution influences teaching performance and learning outcomes. It reviews existing literature on attention management, examines strategies used by effective teachers, and presents empirical findings from a case study on classroom attention distribution. The discussion highlights the implications of these findings for professional development and teacher training programs.